2020
DOI: 10.1002/ece3.7130
|View full text |Cite
|
Sign up to set email alerts
|

QuoVidi: An open‐source web application for the organization of large‐scale biological treasure hunts

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
(22 reference statements)
0
10
0
1
Order By: Relevance
“…Nevertheless, the main limitations are the lack of an objective assessment of learning as result of the gamified activity and the lack of a theoretical framework. Although some studies (Lobet et al, 2020;Patel et al, 2020) reported that the students' knowledge improved after the activity, there was no direct comparison with conventional teaching scenarios. Only Pakinee and Puritat (2021) compared the performance of their students in both situations, showing that gamification made students start working earlier, but there were no differences on their performance in the long term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the main limitations are the lack of an objective assessment of learning as result of the gamified activity and the lack of a theoretical framework. Although some studies (Lobet et al, 2020;Patel et al, 2020) reported that the students' knowledge improved after the activity, there was no direct comparison with conventional teaching scenarios. Only Pakinee and Puritat (2021) compared the performance of their students in both situations, showing that gamification made students start working earlier, but there were no differences on their performance in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…Teaching biology is particularly challenging if the students are not allowed to access laboratories for hands-on observation of fresh specimens and the lockdown restricted movement outside students' home. Lobet et al (2020) developed a biological treasure hunt activity for 346 first-year biology students by using QuoVidi, an open-source web-based platform. This platform was conceived to teach biological vocabulary and to observe the surrounding natural world.…”
Section: Biology Studiesmentioning
confidence: 99%
“…The use of this method has produced positive results in the COVID-19 context ( Nieto-Escamez and Roldán-Tapia, 2021 ; Rincon-Flores and Santos-Guevara, 2021 ). Moreover, gamification has been used in different subjects, such as business ( Pakinee and Puritat, 2021 ), computer sciences ( Liénardy and Donnet, 2020 ), and chemistry learning ( da Silva Júnior et al, 2020a , b ), as well as biological sciences courses, such as biology ( Kalleny, 2020 ; Lobet et al, 2021 ), microbiology ( Dustman et al, 2021 ), physiology ( Moro et al, 2020 ; Hennekes et al, 2021 ; Herkes et al, 2021 ; Kane et al, 2022 ), and medical and nursing education ( Gentry et al, 2019 ; Malicki et al, 2020 ; O’Connell et al, 2020 ; van Gaalen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Por otra parte, existe algún estudio como el de Cameron y Bizo (2019) que muestra resultados contradictorios respecto a la mayor parte del cuerpo base del estudio, señalando que la herramienta utilizada (Kahoot!) no aumentó directamente el rendimiento; en Lobet et al (2021) se señala como punto negativo la duración excesiva que poseía el videojuego pedagógico, aunque se mejoró la motivación del alumnado con su implantación; en Karaaslan (2018) no se produjo aprendizaje porque a los estudiantes no les gustaban los juegos digitales, los consideraban innecesarios o infantiles, no encontrando nada curioso en ellos o porque no sentían atracción por el contenido. En estos casos, se podría recomendar que el alumnado elabore sus propios juegos siguiendo las instrucciones del profesorado o modificarlos según los comentarios constructivos más frecuentes de los estudiantes.…”
Section: Discusión De Los Resultados Y Conclusionesunclassified